PERANCANGAN MEJA TROLI ERGONOMIS DENGAN PENDEKATAN ANTROPOMETRI DAN REBA - Dwi Putra, Adrianus; Lawi, Ansarullah; Syara Nasution, Rivara (Journal of Industrial Engineering and Technology, 2023)
CV XYZ is a company engaged in the field of Bottled Drinking Water. The production process at this company still uses the traditional MMH (Manual Material Handling) method which causes various complaints from employees, so it is necessary to think of an alternative method or tool that can change this manual process. Based on this, this research was conducted to design a tool that can optimize the material handling process and reduce musculoskeletal risks that arise in employees. There are 3 methods used, namely anthropometry, the Nordic Body Map (NBM) questionnaire, and work posture analysis using the REBA method. After testing, it was found that the trolley table that was in accordance with the employee's anthropometry was able to reduce employee complaints by 25% on several parts of the worker's body. From the results of the REBA assessment, a score of 6 (moderate) is obtained if using a table trolley, while without a trolley it produces a score of 12 (has a very high risk). The results of this research are considered to have a significant impact both in optimizing the production system, as well as in terms of employee safety and health from an employee health and safety perspective.